A new species of Bauhinia (Leguminosae) from the state of Jalisco - Reynoso Dueñas, J. Jaqueline (Instituto de Ecología, A.C., 1992)
Bauhinia ramirezii is proposed as a new species, closely related to B. pauletia. The principal differences between B. pauletia and B. ramirezii are the lack of spines, larger leaves, broader white petals with an apical twist and the 10 (not 5) fertile stamens in the latter.